Adenovirus Fibers as Ultra-Stable Vehicles for Intracellular Nanoparticle and Protein Delivery - Chrysoula Kokotidou; Fani Tsitouroudi; Georgios Nistikakis; Marita Vasila; Katerina Papanikolopoulou; Androniki Kretsovali; Anna Mitraki (Biomolecules, 2022)
Protein-based carriers are promising vehicles for the intracellular delivery of therapeutics. In this study, we designed and studied adenovirus protein fiber constructs with potential applications as carriers for the delivery of protein and nanoparticle cargoes. We used as a basic structural framework the fibrous shaft segment of the adenovirus fiber protein comprising of residues 61–392, connected to the fibritin foldon trimerization motif at the C-terminal end. A fourteen-amino-acid biotinylation sequence was inserted immediately after the N-terminal, His-tagged end of the construct in order to enable the attachment of a biotin moiety in vivo. We report herein that this His-tag biotinylated construct folds into thermally and protease-stable fibrous nanorods that can be internalized into cells and are not cytotoxic. Moreover, they can bind to proteins and nanoparticles through the biotin–streptavidin interaction and mediate their delivery to cells. We demonstrate that streptavidin-conjugated gold nanoparticles can be transported into NIH3T3 fibroblast and HeLa cancer cell lines. Furthermore, two streptavidin-conjugated model proteins, alkaline phosphatase and horseradish peroxidase can be delivered into the cell cytoplasm in their enzymatically active form. This work is aimed at establishing the proof-of-principle for the rational engineering of diverse functionalities onto the initial protein structural framework and the use of adenovirus fiber-based proteins as nanorods for the delivery of nanoparticles and model proteins. These constructs could constitute a stepping stone for the development of multifunctional and modular fibrous nanorod platforms that can be tailored to applications at the sequence level.